Baseline characteristics of patients with heart failure with preserved ejection fraction in the EMPEROR-preserved trial - Anker, Stefan; Butler, Javed; Brückmann, Martina; Pocock, Stuart J.; Zannad, Faiez; Packer, Milton (European journal of heart failure, 2020)
Aims EMPEROR-Preserved is an ongoing trial evaluating the effect of empagliflozin in patients with heart failure with preserved ejection fraction (HFpEF). This report describes the baseline characteristics of the EMPEROR-Preserved cohort and compares them with patients enrolled in prior HFpEF trials. Methods and results EMPEROR-Preserved is a phase III randomized, international, double-blind, parallel-group, placebo-controlled trial in which 5988 symptomatic HFpEF patients [left ventricular ejection fraction (LVEF) >40%] with and without type 2 diabetes mellitus (T2DM) have been enrolled. Patients were required to have elevated N-terminal pro B-type natriuretic peptide (NT-proBNP) concentrations (i.e. >300 pg/mL in patients without and >900 pg/mL in patients with atrial fibrillation) along with evidence of structural changes in the heart or documented history of heart failure hospitalization. Among patients enrolled from various regions (45% Europe, 11% Asia, 25% Latin America, 12% North America), the mean age was 72 ± 9 years, 45% were women. Almost all patients had New York Heart Association class II or III symptoms (99.6%), and 23% had prior heart failure hospitalization within 12 months. Thirty-three percent of the patients had baseline LVEF of 41-50%. The mean LVEF (54 ± 9%) was slightly lower while the median NT-proBNP [974 (499-1731) pg/mL] was higher compared with previous HFpEF trials. Presence of comorbidities such as diabetes (49%) and chronic kidney disease (50%) were common. The majority of the patients were on angiotensin-converting enzyme inhibitors/angiotensin receptor blockers/angiotensin receptor-neprilysin inhibitors (80%) and beta-blockers (86%), and 37% of patients were on mineralocorticoid receptor antagonists. Conclusion When compared with prior trials in HFpEF, the EMPEROR-Preserved cohort has a somewhat higher burden of comorbidities, lower LVEF, higher median NT-proBNP and greater use of mineralocorticoid receptor antagonists at baseline. Results of the EMPEROR-Preserved trial will be available in 2021.
Gesehen am 04.12.2024